APPENDING ROLES OF THAI LANNA TEMPLES FOR SUSTAINABLE COMMUNITIES: A CASE STUDY OF WAT PHUMIN, NAN PROVINCE - Tawipas Pichaichanarong; Veerawat Sirivesmas; Rueanglada Punyalikhit, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Temples have been important in Thai society for over 700 years. When the Sukhothai Kingdom (1238 -1438 AD) was the capital city of Thailand. The great King Ramkamhang had been accepted Theravada Buddhism to be the strongest religion in the land. Later Lanna kingdom (1296 - 1558 AD) was founded in the mid-13th century by King Mangrai. Indeed, King Ramkamhang was friends with King Mangrai, and King Ngam Muang of Phayao Kingdom (1094–1338 AD), it is possible Theravada Buddhism had been introduced to the kingdoms during the reigns of these three Kings. Indeed, the Lanna Kingdom has accepted Theravada Buddhism to be their religion. Until 1894, Lanna Kingdom combined with Siam Kingdom which is the Rattanakosin period (1782 AD - present). Throughout history, temples have become an essential part of Lanna and Thais’ lives. At present, some Thai Lanna temples are not only functions for performing religious rites, but also, they become central for Lanna and Thai communities. Temple (“Wat” in Thai) is a sacred architecture. Moreover, there are ideas to decorate inside temples with arts. Wattana Boonjub (2009) points out that Mural painting is used to teach (Lanna and) Thai people in the past. For example, Wat Phumin, Nan province. With beautiful Lanna architecture and exquisite Lanna mural paintings, these are intangible heritages. These unique characteristics have invited lots of people to visit this temple for years. Therefore, Wat Phumin became a tourist attraction that creates revenue for its community. Johan Galtung (1980) gave the definition for “Self-Reliance”, is the strategy for development to be financial independence. With collaboration from the community, it becomes a sustainable community. For Methodology, quantitative and qualitative methods were used by collecting the data from tourists who have been visited Wat Phumin, Nan province. The data then were analyzed using mean, descriptive statistics, and qualitative data. This study concludes that Wat Phumin, Nan province has created a sustainable community for its community.